ESTRO consensus guideline on target volume delineation for elective radiation therapy of early stage breast cancer. Issue 1 (January 2015) - Offersen, Birgitte V.; Boersma, Liesbeth J.; Kirkove, Carine; Hol, Sandra; Aznar, Marianne C.; Biete Sola, Albert; Kirova, Youlia M.; Pignol, Jean-Philippe; Remouchamps, Vincent; Verhoeven, Karolien; Weltens, Caroline; Arenas, Meritxell; et al.
Abstract Background and purpose Delineation of clinical target volumes (CTVs) is a weak link in radiation therapy (RT), and large inter-observer variation is seen in breast cancer patients. Several guidelines have been proposed, but most result in larger CTVs than based on conventional simulator-based RT. The aim was to develop a delineation guideline obtained by consensus between a broad European group of radiation oncologists. Material and methods During ESTRO teaching courses on breast cancer, teachers sought consensus on delineation of CTV through dialogue based on cases. One teacher delineated CTV on CT scans of 2 patients, followed by discussion and adaptation of the delineation. The consensus established between teachers was sent to other teams working in the same field, both locally and on a national level, for their input. This was followed by developing a broad consensus based on discussions. Results Borders of the CTV encompassing a 5 mm margin around the large veins, running through the regional lymph node levels were agreed, and for the breast/thoracic wall other vessels were pointed out to guide delineation, with comments on margins for patients with advanced breast cancer. Conclusion The ESTRO consensus on CTV for elective RT of breast cancer, endorsed by a broad base of the radiation oncology community, is presented to improve consistency.